2021
DOI: 10.1021/acs.inorgchem.1c00201
|View full text |Cite
|
Sign up to set email alerts
|

HKUST-1 Metal Organic Framework as an Efficient Dual-Function Catalyst: Aziridination and One-Pot Ring-Opening Transformation for Formation of β-Aryl Sulfonamides with C–C, C–N, C–S, and C–O Bonds

Abstract: Metal−organic frameworks (MOFs) are extensively used in catalysis due to their robust structure, well-defined periodic reaction centers, and high porosity. We report Cu 3 (BTC) 2 •(H 2 O) 3 (HKUST-1) as an efficient heterogeneous catalyst for aziridination of alkene and ring-opening reaction of activated aziridines. Furthermore, we demonstrate that the transfer of a nitrogen group from PhINTs to olefins and its analogue to give aziridines takes place at the coordinatively unsaturated Cu(II) site of Cu 3 (BTC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 106 publications
0
30
0
Order By: Relevance
“…The empty coordination sites on the metal ions of the Ni– PTA′ would be beneficial to activate substrates for synergistic catalysis with photoredox catalysts. 53 The Fourier transform infrared (FT-IR) spectroscopy of the crystals also did not exhibit any significant changes before and after the activation of Ni– PTA , except for the loss of the characteristic peaks of the O–H bands (about 3690–3314 cm −1 ) for the water molecules (Fig. 2c).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The empty coordination sites on the metal ions of the Ni– PTA′ would be beneficial to activate substrates for synergistic catalysis with photoredox catalysts. 53 The Fourier transform infrared (FT-IR) spectroscopy of the crystals also did not exhibit any significant changes before and after the activation of Ni– PTA , except for the loss of the characteristic peaks of the O–H bands (about 3690–3314 cm −1 ) for the water molecules (Fig. 2c).…”
Section: Resultsmentioning
confidence: 91%
“…2c). 53 Moreover, the color changed from green in Ni-PTA to yellow in activated Ni-PTA′, which reverted to its initial color upon exposure to air and moisture (Fig. 2b).…”
Section: Preparation and Characterization Of Dye-functionalized Nicke...mentioning
confidence: 96%
See 1 more Smart Citation
“…HKUST-1 (Cu 3 (BTC) 2 ) is one of the wellstudied porous materials in a broad range of practical applications such as gas adsorption and separation or heterogeneous catalysis. [190][191][192][193] HKUST-1 is assembled from copper-based paddle wheel units connected together by trimesic acid. Pichon et al reported the quantitative formation of [Cu 3 (-BTC) 2 ]$xH 2 O through neat grinding of Cu(OAc) 2 $H 2 O and H 3 BTC for 20 min.…”
Section: Other Mof Materialsmentioning
confidence: 99%
“…They have found extensive applications in gas adsorption and separation, catalysis, and sensor, by virtue of their ultrahigh surface areas, pore volumes and tunable properties [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, CuBTC [Cu 3 (BTC) 2 (H 2 O) 3 ] n (BTC = benzene-1,3,5-tricarboxylate) (also known as HKUST-1) is one of the most studied MOFs [ 14 , 15 , 16 ], and is composed of dimeric cupric tetracarboxylate units, constructed by Cu 2 paddlewheel clusters linked by BTC 3− ligands [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Attributed to its structural characteristics, CuBTC not only has a high specific surface area and pore structure, but also has abundant active centers, making it suited to potential applications in gas adsorption, catalysis and other fields [ 24 ].…”
Section: Introductionmentioning
confidence: 99%